Physicochemical and nutritional properties of rice as affected by parboiling steaming time at atmospheric pressure and variety - Zohoun, E.V.; Tang, E.N.; Soumanou, M.M.; Manful, J.; Akissoe, N.H.; Bigoga, J.; Futakuchi, K.; Ndindeng, S.A. (Wiley, 2018)
To elucidate the effect of different parboiling steaming time on the physicochemical and nutritional quality of rice, four varieties, NERICA1, NERICA7, IR841, and WITA4, were soaked at the same initial temperature (85°C) and steamed for 5, 15, 25, 35, and 45 min. NERICA7 steamed for 25 min recorded the highest head rice yield (71.9%). Nonparboiled IR841 recorded the shortest cooking time (17.0 min), while NERICA1 steamed for 35 min recorded the longest cooking time (26.1 min). NERICA1 steamed for 45 min was the hardest (63.2 N), while nonparboiled IR841 was the softest (28.7 N). NERICA7 recorded higher peak and final viscosities across all steaming times compared to the other varieties. NERICA7 steamed for 35 and 45 min recorded the lowest total starch (77.3%) and the highest protein (13.2%) content, respectively. NERICA7 steamed for 25 and 45 min recorded the highest phosphorus (0.166%), magnesium (572 mg/kg), and potassium (2290 mg/kg) content, respectively. We conclude that, depending on desired physicochemical and nutritional properties, specific varieties and steaming times can be selected to achieve those outcomes.